Area deprivation, individual socioeconomic position and smoking among women in South Korea. Issue 5 (30th July 2010) - Park, Eun-Ja; Kim, Ho; Kawachi, Ichiro; Kim, Il-Ho; Cho, Sung-Il
Abstract : Background: The objective of this study was to examine how area deprivation and individual socioeconomic position affect smoking among women using national survey data. Methods: Smoking and individual sociodemographic characteristics were gathered from the Third Korea National Health and Nutrition Examination Survey, 2005. The Carstairs index was derived for each area using the 2005 census data. The data were analysed using multilevel logistic regression models. Results: After adjusting for age and marital status, low education and manual jobs were significantly associated with a higher likelihood of smoking. In addition, the effect of manual jobs on smoking was modified by area deprivation. When individual occupation and area deprivation were examined together, results indicated that women with manual occupation had much greater odds of smoking when they lived in the least-deprived areas (OR, 4.03; CI, 2.00 to 8.14) than did women with manual job who lived in the middle- or most-deprived areas (OR, 2.19; CI, 1.15 to 4.16), compared to the reference group (housewives in the middle- or most-deprived areas). Conclusion: The results of the present study show that among Korean women, manual work is associated with smoking, and the association is strongest among those living in the least-deprived areas. This interaction between manual work and area deprivation resulted in a higher smoking prevalence among women in affluent urban areas.